Crystal structure of bis[(acetato-κO)(imidazolidine-2-thione-κS)bis(triphenylphosphane-κP)silver(I)] di-μ-imidazolidine-2-thione-κ(4) S:S-bis[(imidazolidine-2-thione-κS)bis(triphenylphosphane-κP)silver(I)] diacetate acetonitrile disolvate tetrahydrate - Nimthong-Roldán, Arunpatcha (Acta Crystallogr E Crystallogr Commun, 2016)
In the title compound, [Ag(2)(C(3)H(6)N(2)S)(4)(C(18)H(15)P)(2)](C(2)H(3)O(2))(2)·[Ag(C(2)H(3)O(2))(C(3)H(6)N(2)S)(C(18)H(15)P)(2)](2)·2C(2)H(3)N·4H(2)O, the Ag(I) ion in the mononuclear neutral complex exhibits a distorted tetrahedral environment with coordination by two P atoms from triphenylphosphane (PPh(3)) ligands, one S atom of an imidazolidine-2-thione (etu) ligand and one O atom of an acetate anion. The binuclear cationic complex comprises two inversion-related [Ag(C(3)H(6)N(2)S)(2)(C(18)H(15)P)] units with Ag(I) ions bridged by two S atoms from etu ligands forming a four-membered Ag–S–Ag–S ring. Each Ag(I) ion is coordinated by a P atom of a PPh(3) ligand, two S atoms of bridging etu ligands and the terminal S atom of an etu ligand in a distorted tetrahedral environment. In the crystal, the mononuclear complex is linked to lattice water molecules through O—H⋯O and N—H⋯O hydrogen bonds, forming a chain along [100]. In addition, the binuclear complex molecules are connected to acetate anions and lattice water molecules via O—H⋯O, N—H⋯O and O—H⋯S hydrogen bonds, also along [100].